Impact of TiO2 content on Titanium oxide supported chitosan photocatalytic system to treat organic dyes from wastewater - Muhd Julkapli, Nurhidayatullaili (Malaysian Catalysis-An International Journal, 2021)
Titanium dioxide (TiO2) nanoparticles are used enormously for treating wastewater pollutants due to their unique optoelectronic and physiochemical properties. Though, wide bandgap, fast recombination of e- - h+ pair, and low adsorption toward organic pollutants limit their applications. However, immobilization of TiO2 on Chitosan (Cs) is believed to overcome these limitations. Cs with plenty of NH2 and OH groups in their structure are expected to enhance their adsorption and consequently photocatalytic performance. A series of TiO2/Cs photocatalysts have been prepared using a chemical co-precipitation method. Amount of TiO2 is varied from 0.25, 0.50, and 0.75 to 1.0 g. The photocatalysts are characterized by using FESEM-EDS, CHNS Elemental Analyser TGA, FTIR, and UV-Vis spectroscopy. These characterization results revealed the formation of a good interface between TiO2 and Cs matrix. Increasing TiO2 content significantly increased the thermal stability of the photocatalyst up to 600ᵒC. The photocatalytic activity of Cs/TiO2 is observed under UV light which is found to be more significant with 1:1(TiO2: Cs) composition for the degradation of methylene blue dye at 85 % and be maintained up to 4 numbers of cycles. This demonstrated open new insight into the application of Cs as a support materials and adsorption agent in TiO2 based photocatalyst system